2022
DOI: 10.1039/d2sc01563c
|View full text |Cite
|
Sign up to set email alerts
|

Directed, nickel-catalyzed 1,2-alkylsulfenylation of alkenyl carbonyl compounds

Abstract: We report a regioselective, nickel-catalyzed syn-1,2-carbosulfenylation of non-conjugated alkenyl carbonyl compounds with alkyl/arylzinc nucleophiles and tailored N–S electrophiles. This method allows the simultaneous installation of a variety of C(sp3) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This endeavor has been very productive, leading to a series of publications and pushing the state of the art in the directing-auxiliary-free diarylation of alkenyl amides, carboxylates and ketones, for example. Through our work in this field, we learned the importance of an electron-deficient olefin, showcasing the ability of Ni­(cod)­(DMFU) to serve as a catalyst in challenging diarylations . While the initial goal of the precatalyst project was to develop Ni(0) complexes that were more stable but otherwise functionally equivalent to Ni­(cod) 2 , we and others have found that quinone-ligated nickel centers possess unique reactivity in important reactions, such as the aforementioned difunctionalization of alkenes and nickel-catalyzed C–N couplings, which is a phenomenon we are now exploring in depth through our collaboration.…”
Section: Earth-abundant Metals As Replacements For Palladiummentioning
confidence: 99%
“…This endeavor has been very productive, leading to a series of publications and pushing the state of the art in the directing-auxiliary-free diarylation of alkenyl amides, carboxylates and ketones, for example. Through our work in this field, we learned the importance of an electron-deficient olefin, showcasing the ability of Ni­(cod)­(DMFU) to serve as a catalyst in challenging diarylations . While the initial goal of the precatalyst project was to develop Ni(0) complexes that were more stable but otherwise functionally equivalent to Ni­(cod) 2 , we and others have found that quinone-ligated nickel centers possess unique reactivity in important reactions, such as the aforementioned difunctionalization of alkenes and nickel-catalyzed C–N couplings, which is a phenomenon we are now exploring in depth through our collaboration.…”
Section: Earth-abundant Metals As Replacements For Palladiummentioning
confidence: 99%
“…C–S bond formation via the reductive elimination regenerated the active Ni( i ) catalyst ( 244 ). Soon after that, the Engle group 72 further expanded the scope of the nucleophile to C(sp 3 ) partners and developed the 1,2-alkylsulfenylation of unactivated alkenes with alkylzinc reagents and the sulfonamide sulfenyl electrophiles. To surrogate the above mentioned undesired process and the β-hydride elimination of alkyl nucleophile, a stronger bidentate directing auxiliary (8-aminoquinoline, AQ) was employed.…”
Section: Transition-metal Catalyzed Carbosulfenylationmentioning
confidence: 99%